THE LEVEL OF SEROTONIN IN PATIENTS WITH GENERALIZED ATHEROSCLEROSIS AND ITS DYNAMICS UNDER THE INFLUENCE OF CILOSTAZOL - Motsak, Tatiana; Lizogub, Victor; Kupchynska, Elena; Bugaytsev, Alexey (The Ukrainian Scientific Medical Youth Journal, 2020)
The aim of this work is to study the effect of cilostazol on regional hemodynamics, sero- tonin levels and functional activity of the brain, heart, lower extremities in patients with generalized atherosclerosis. A 12-week open-label, randomized, placebo-controlled study included 52 males with generalized atherosclerosis and 26 males with chronic coronary syndrome (comparison group). Pa- tients in the generalized atherosclerosis group were randomized into two subgroups: 26 males in ad- dition to basic therapy received cilostazol at a dose of 100 mg twice daily, and 26 patients who received additional placebo. Patients with generalized atherosclerosis had injury of four vascular territories: cerebral, coronary, mesenteric and lower extremities. It was found that in patients with generalized atherosclerosis, the level of serotonin in plasma exceeded this comparison group by 7.8 times, and a number of indicators were lower - in particular, indicators of volumetric blood flow (p<0,001), cognitive function, painless walking distance. Under the influence of treatment with the addition of cilostazol for 12 weeks before baseline therapy, the condition improved: plasma serotonin levels de- creased 2,9 times (p<0,001), significantly (p<0,001) increased volumetric bold flow in all studied vas- cular territories, which contributed to a decrease in the number of both painful and painless episodes of myocardial ischemia (according to daily electrocardiographic monitoring), increased painless and maximum walking distance, and improved cognitive function of the brain. In the generalized ath- erosclerosis group, who was taking placebo, under the influence of treatment, the changes were not significant. Our data indicate a positive effect of cilostazol as an addition to basic therapy in patients with generalized atherosclerosis and the need for further research in this area.